2015
DOI: 10.1007/s10661-015-4973-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of heavy metals concentration in topsoil of urban green space and agricultural land uses

Abstract: The main objective of this study was to determine the concentration of cadmium, chromium, copper, nickel, lead, and zinc in surface soils of two land uses including agricultural and urban green space in Semnan Province, Iran. For this purpose, the soil samples of 27 urban green space and 47 agricultural fields were collected and analyzed. The correlation coefficients, analysis of variance, principal component analysis, cluster analysis, and geoaccumulation index were utilized to compare the mean values in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The PTE levels obtained in this studied were compared with data reported by other studies carried out for agricultural soils in Iran (Table 2). When compared with the results of previous studies in Iran e.g., [13,40,41,[43][44][45][46][47], average values are similar or lower to indicate by them, probably due to some of these studies were carried out near to industrial areas e.g., [40,41]. Results showed significant enrichment of Cr and Ni in studied agricultural lands, although with similar values as indicated by Doabi et al [13] for agricultural areas in Kermanshah province, Western Iran.…”
Section: Soil Physicochemical Properties and Pte Levels In Studied Soilssupporting
confidence: 69%
“…The PTE levels obtained in this studied were compared with data reported by other studies carried out for agricultural soils in Iran (Table 2). When compared with the results of previous studies in Iran e.g., [13,40,41,[43][44][45][46][47], average values are similar or lower to indicate by them, probably due to some of these studies were carried out near to industrial areas e.g., [40,41]. Results showed significant enrichment of Cr and Ni in studied agricultural lands, although with similar values as indicated by Doabi et al [13] for agricultural areas in Kermanshah province, Western Iran.…”
Section: Soil Physicochemical Properties and Pte Levels In Studied Soilssupporting
confidence: 69%
“…Since 1997 till 2015, the average value of As, Hg, Zn, Cu, Co, Ni, Cr, Pb, and Cd decreased above (Banasová & Lackovičová 2004;Hronec et al 2008) with positive impact on the environmental situation within the study area. But due to the fact, that heavy metals are non-biodegradable, they remain accumulated in the soil for years (Mehrabi et al 2015;Mirzaei et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Higher concentration of total Fe was found in the fallow land and the lower concentration was found 1). However, many studies indicated that farmlands usually exhibited significantly higher heavy metal contents compared to other land use types due to the continuous application of agrochemicals [30][31]. The heavy metal fractions in various land systems varied in order of fallow>pasture >crop>forest.…”
Section: Resultsmentioning
confidence: 99%